Relationships between 16-18-Year-Old Students' Participation in Extracurricular Activities and Their Pro-Social Behaviour as Well as Their Value Orientations - Lina Baltakienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Extra-curricular activities are concurrent with personality development, often  named  as  assumption  to  pro-social  behaviour  and  analysed  considering  value  orientation.  The  following hypothesis was set in the study: indexes of expression of pro-social behaviour and value orientation were more characteristic of students involved in extra-curricular activities in comparison with non-active (after school) students. Type of extra-curricular activities was included in the analysis. Research  aim. The aim of the study was to analyse relationships between students' participation in extra- curricular activities and expression of pro-social behaviour as well as their value orientation. Research methods. The sample consisted of 179 students (82 girls and 97 boys) at the age of 16-18 years. Written survey was applied for the research. The participants completed the Pro-social Tendencies Measure (Carlo et al., 2003) and S. H. Schwartz's (1992) value orientation methodology. Participation in extra-curricular activities was assessed by asking question with a detailed list of structured activities. Research  results.  Results  of  the  study  revealed  that  there  were  no  links  between  students'  participation  in extra-curricular activities and pro-social behaviour. However, it was determined that public assistance was more characteristic of students participating in artistic extra-curricular activities in comparison to students that attended sports  activities  after  school. The  same  situation  was  with  value  orientation:  there  was  absence  of  correlations between students' participation in extra-curricular activities and value orientation, but significant differences related to the type of extra-curricular activities were found. Self-transcendence was more important to students that attended artistic extra-curricular activities in comparison with students participating in sports activities after school. Discussion and conclusion. Tendencies of results of this research are comparable to those in other scientific studies.  Studies  that  examined  participation  in  extra-curricular  activities  and  value  orientations  of  interfaces  in Lithuania are still missing. Keywords: value orientation, students' participation in extra-curricular activities, pro-social behaviour.